HUBUNGAN PARITAS DAN UMUR IBU DENGAN KEJADIAN HIPEREMESIS GRAVIDARUM DI RSUD ADJIDARMO RANGKASBITUNG TAHUN 2011 - Ruri Puriati; Nurul Misbah (Akademi Kebidanan La Tansa Mashiro, 2014)
According to the 2001 Household Health Survey, direct obstetric causes a 90% majority of bleeding (28%) and infections (11%). Indirect cause of maternal death in the form of health conditions such as lack of energy suffered chronic (37%). Researchers interested in studying the relationship of parity and maternal age with hyperemesis gravidarum events in Dr. Adjidarmo Rangkasbitung in 2011. The study design used is analytic (quantitative) case-control type. The population in this research that pregnant women in Dr. Adjidarmo Rangkasbitung the period January to December 2011 as many as 609 people. In this study consisted of a sample of cases and controls with a total sample of 237 respondents. From the test results are statistically significant association between parity and age with hyperemesis gravidarum. It required health education to pregnant women by health workers at each ANC visit, one of them detects a problem that can be complications in pregnancy such as hyperemesis gravidarum.